PERUBAHAN SOSIAL DAN BUDAYA MASYARAKAT DI GAMPONG GUNONG KLENG AKIBAT KEMAJUAN ILMU PENGETAHUAN DAN TEKNOLOGI - zurhanli Zurhanli (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2022)
Socio-cultural change is a symptom of changing social and cultural conditions in a society, both in terms of increasing social strata and how to accept the development or progress of the times in society. Socio-cultural change is a symptom that always occurs in every society. This research aims to; 1) describe the environmental conditions of Gampong Gunong Kleng. 2) describe the social activities of the community due to advances in science and technology. 3) describe the causes of socio-cultural changes in society in the context of scientific and technological advances. 4) describe the impact of socio-cultural changes on the people of Gampong Gunong Kleng. Data were collected using interview techniques, as well as literature review, from books and journals related to socio-cultural changes due to advances in science and technology. The results of this study are: 1) local wisdom that occurs in the Gampong Gunong Kleng community is a community tradition that contains values and has been carried out for a long time from generation to generation, and has undergone changes. With the progress of science and technology in the form of ideas and activities as well as about the relationship between humans and God, humans and humans and their relationship with the environment. 2) the community views the importance of good social relations, and continues to maintain harmony. 3) there are causal factors and impacts of socio-cultural changes in gampong/village communities which result in differences in socio-cultural conditions in the previous year.